Design recommendation of a care center to overcome the psychological and behavioral impact of infectious diseases on humans: 10.55131/jphd/2023/210320 - Khan, Shamim; Fatima Kaafil, Shifana (Journal of Public Health and Development, 2023)
The Covid 19 pandemic threatened the life of individuals, and there was a lack of information on treatment, handling of patients and disposal of waste. The psychological and behavioral impact on humans due to outbreak of Covid is studied and based on that, a person-centered care center is suggested. The research methodology used are surveys and interviews among stake holders. Based on the surveys and interviews conducted during the pandemic, it is found that 94% of the respondents prefer to use private vehicles with at least one member to accompany them. People prefer to use 3 ply facemasks, followed by cotton masks and N95 masks. Existing literature discusses the physical effects on individuals. This paper focuses on psychological and behavioral changes. Based on the study, person centered a care center is recommended with facilities to treat patients with different levels of infections and a counselling center for the persons suffering from Covid and other infectious diseases.